Self-healing systems and wireless networks management - Chaudhry, Junaid Ahsenali (CRC Press, 2014)
"A self-healing network has a network architecture that can withstand a failure in its transmission paths. The biggest issue, to date, in self-healing systems is fault identification and its classification. This book uses the techniques of casual reasoning to classify the candidate faults from the fault identification process. It employs a similarity matrix in order to match the user activity log and its pattern in a transformed space. I then describes how to embed the self-healing policy, so the if the client has more faults related to the previous one, they can be dealt with at the client side"--